DEVELOPMENT AND USE OF DIFFERENT FORMULATIONS OF PSEUDOMONAS FLUORESCENS SIDEROPHORE FOR THE ENHANCEMENT OF PLANT GROWTH AND INDUCTION OF SYSTEMIC RESISTANCE AGAINST PYRICULARIA ORYZAE IN LOWLAND RICE - P. AMUTHARAJ; C. SEKAR; S. ESATH NATHEER (International Journal of Pharma and Bio Sciences, 2013)
The application effect of different formulations of Pseudomonas fluorescens siderophore viz., control, Pseudomonas fluorescens cells alone, Pseudomonas fluorescens + Fe + siderophore complex, Siderophore alone, Fe + siderophore complex alone and challenge inoculation of Pyricularia oryzae on the enhancement of growth and yield parameters and ISR mediated biocontrol against Pyricularia oryzae in lowland rice cv.IR-50 was studied under pot culture condition. It was observed that the application of different formulations P. fluorescens siderophore augmented the growth and yield parameters viz., plant height, shoot and root dry weight, chlorophyll content and reduced the blast disease incidence in lowland rice crop to a marked level, but with variation among them. Interestingly, the application of P. fluorescens cells along with their Fe + siderophore complex augmented the above said parameters to a higher level followed by Fe + siderophore complex alone, siderophore alone, P. fluorescens cells alone treatments. Moreover, the same treatment altered the biochemical constituent viz., total and OD phenol content, reducing and non-reducing sugar levels and physiological activities viz., PO and PPO levels of rice plant to a higher level when compared to other treatments and suggesting the induction of systemic resistance in the host plant against the phytopathogen viz., Pyricularia oryzae. The results of the present study clearly revealed the role of physiological status of the microorganism in siderophore mediated plant growth stimulation and induction of systemic resistance against Pyricularia oryzae in lowland rice.